Diversity of experience and labor productivity in creative industries - Orsa Kekezi (Journal for Labour Market Research, 2021)
This paper studies how the previous experience among workers relates to the labor productivity of the creative industries in Sweden. Effective knowledge transfers are dependent on the cognitive distance among employees. Using longitudinal matched employer-employee data, I measure the portfolio of the skills within a workplace through (i) the workers' previous occupation, and (ii) the industry they have been working in previously. Estimates show that diversity of occupational experience is positive for labor productivity, but the diversity of industry experience is not. When distinguishing between related and unrelated diversity, the relatedness of occupational experience is positive for labor productivity, while unrelated occupational experience instead shows negative relationship with productivity. These results point towards the importance of occupational skills that workers bring with them to a new employment, for labor productivity.
Keywords: J24; L25; 330; Diversity; Skill relatedness; Previous experience; Labor mobility; Knowledge spillovers